1974
DOI: 10.1104/pp.53.3.426
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Responses of Wheat Mitochondrial Membranes to Growth at Low Temperatures

Abstract: The responses in membrane lipid composition, structure, and function of four cultivars of wheat (Triticum aestivum L.) to growth at Differences in cold tolerance between hardy and nonhardy plant species may reside partially in the ability of the intracellular membranes to adapt to low temperatures (7,10,11,22,23). Mitochondria were selected for a comparison of the structural and functional characteristics of membrane components of four wheat varieties which exhibit quantitatively different degrees of cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 26 publications
(30 reference statements)
4
41
0
Order By: Relevance
“…The observation that ca-ketoglutarate in the presence of ADP is oxidized rapidly with good respiratory control and close to theoretical ADP/O ratios (14) suggests that processes other than those normally associated with respiration are involved in mitochondrial contraction. This is supported further by the rapid decline observed in the contraction response when seedlings are grown at 2 C or transferred from 24 to 2 C, although previous studies (11) have demonstrated good respiratory properties of mitochondria isolated from 2 C grown seedlings. These observations may be related to the loss of NADH-induced contraction of mitochondria from drought-stressed corn seedlings (4), since many similarities exist between changes which occur during cold and drought stress.…”
Section: Methodsmentioning
confidence: 55%
See 3 more Smart Citations
“…The observation that ca-ketoglutarate in the presence of ADP is oxidized rapidly with good respiratory control and close to theoretical ADP/O ratios (14) suggests that processes other than those normally associated with respiration are involved in mitochondrial contraction. This is supported further by the rapid decline observed in the contraction response when seedlings are grown at 2 C or transferred from 24 to 2 C, although previous studies (11) have demonstrated good respiratory properties of mitochondria isolated from 2 C grown seedlings. These observations may be related to the loss of NADH-induced contraction of mitochondria from drought-stressed corn seedlings (4), since many similarities exist between changes which occur during cold and drought stress.…”
Section: Methodsmentioning
confidence: 55%
“…A recent study (16) into the effect of temperature on respiration of mitochondria from the same four cultivars grown at 2 and 24 C revealed no correlation between cold hardiness of the cultivars and the transition temperatures for mitochondrial and tissue segment respiration. The observed increase in fatty acid unsaturation of both mitochondrial membranes (11) and total membranes (1) (1,11,15,17), has failed to establish a correlation between cold hardiness and changes in the structural and functional properties of mitochondria and other cell membranes. It has generally been shown that numerous changes occur in the cell which are associated with growth at low temperature but not with the development of cold hardiness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of chilling injury in various tissues has been related to phase changes in the mitochondrial membranes and the degree of unsaturation of the fatty acids of the tissue (3,4,9). Cold-acclimatized wheat plants had increased levels of linolenic acid (6), and a marked decrease in the percentage of unsaturated acids of various chilling-sensitive plants occurred after the plants were exposed to chilling temperatures (13). It has been suggested that the phenomenon of chilling injury cannot be explained entirely by fatty acid composition (6,13).…”
mentioning
confidence: 99%